2019
DOI: 10.3390/agronomy9110718
|View full text |Cite
|
Sign up to set email alerts
|

Processing Tomato–Durum Wheat Rotation under Integrated, Organic and Mulch-Based No-Tillage Organic Systems: Yield, N Balance and N Loss

Abstract: In a 4-year study, the biannual crop rotation processing tomato–durum wheat was applied to three cropping systems: (i) an innovative organic coupled with no-tillage (ORG+) where an autumn-sown cover crop was terminated by roller-crimping and then followed by the direct transplantation of processing tomato onto the death-mulch cover; (ii) a traditional organic (ORG) with autumn-sown cover crop that was green manured and followed by processing tomato; and (iii) a conventional integrated low-input (INT) with bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In particular the rational management of soil can increase water use efficiency either through decreasing soil evaporation, using artificial [13][14][15] or natural [16,17] mulching material, and increasing soil water holding capacity, via decompaction and organic matter enrichment. Recent experiences in horticultural crops [18,19] reported that water and N recycling at agroecosystem level can be enhanced by cover crop practice and natural mulching covering techniques, independently from the soil management strategy. The authors pointed out that the improved nitrogen surplus was not sufficiently retained in the agroecosystem without cover crop.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the rational management of soil can increase water use efficiency either through decreasing soil evaporation, using artificial [13][14][15] or natural [16,17] mulching material, and increasing soil water holding capacity, via decompaction and organic matter enrichment. Recent experiences in horticultural crops [18,19] reported that water and N recycling at agroecosystem level can be enhanced by cover crop practice and natural mulching covering techniques, independently from the soil management strategy. The authors pointed out that the improved nitrogen surplus was not sufficiently retained in the agroecosystem without cover crop.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also important to note that a positive N balance can also indicate a higher risk of N leaching, because N surplus and, in case of mineralisation, enhanced soil N availability could potentially be lost if not synchronized with crop needs. On the other hand, one advantage of legume derived N is that it is generally less prone to leaching than mineral N, as organic N is better retained in the soil (Crews and Peoples, 2005;Tosti et al, 2019). Thus even if an important fraction is not recovered in the crop (Almeida Acosta et al, 2011), it has a lower potential to be lost in the environment in contrast to mineral fertilizers (Hansen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…rainfall or irrigation); iii) the soil hydraulic characteristics. Nitrate leaching losses (and the associated potential risk of groundwater contamination) from intensive vegetable production has been studied extensively in a wide variety of pedo-climatic conditions and cropping systems (e.g., Thompson et al, 2007;Farneselli et al, 2018;Tosti et al, 2019;Rakotovololona et al, 2019;de Haan et al, 2019;Hefner et al, 2019).…”
Section: Nitrate Leachingmentioning
confidence: 99%